Proměny funkcé obecne češtiny při stylizaci textů - Krćmova, Marie (Stylistyka, 2021)
The article deals with generał problems conceming specific means of expression from the diachronic point of view, using Common Czech (obecna ćeStina) as an example. It is especially emphasized that during the analysis a complex approach is of particular impor- tance, morę than from the synchronic point of view, also with regard to stylistic examina- tions. When scholars focusing on this particular discipline choose their theoretical background, they should also take into consideration concepts and definitions of Common Czech from both linguistic and sociolinguistic points of view in various periods. They should also choose only relevant means of expression, with sufficient frequency. Furthermore, they need to find texts the stylistic norm of which provides an opportunity to use Common Czech, to some extent or fully (today as well as in the past). Ali these aspects are significant, although their hierarchy may be varied; using identical materiał, it is thus possible to arrive at different generalizations.